The Effectiveness of Coping Skills in Improving Critical Thinking Skills of Junior High School Students - Mukhamad Fadhir; Sigit Sanyata (Universitas PGRI Yogyakarta, 2026)
Coping skills are more widely used to address a range of problems and emotional issues. However, there is no information on the impact of improving critical thinking skills. This study examined the effectiveness of coping skills in improving the critical thinking ability of Muhammadiyah 10 Yogyakarta junior high school students. This study used a quasi-experimental design measurements were taken before and after the intervention using the California Critical Thinking Skills Test (CCTST) with a reliability of 0.883. The results of the N-Gain Score analysis showed that the average score of the experimental group was 85.97% (effective category), while the control group was 68.47% (moderately effective category). Individual scores in the experimental group ranged from 77.05% to 98.61%, while the control group ranged from 54.17% to 83.56%. These findings indicate that coping skills are significantly effective in improving students' critical thinking ability. Keywords: critical thinking skills, coping skills, junior high school